Genotype by environment interaction iin Lolium perenne: Grouping wild populations by cluster analysis - Oliveira, J.A.=700 1 Charmet, G.
(Es, En)
ilus., 20 ref.
Keywords: LOLIUM PERENNE; INTERACCION GENOTIPO AMBIENTE; CLASIFICACION; ESPAÑA; RAIGRAS INGLES; CLASIFICACION ASCENDENTE JERARQUICA